2015
DOI: 10.1289/ehp.1408217
|View full text |Cite|
|
Sign up to set email alerts
|

Association between Lung Function in Adults and Plasma DDT and DDE Levels: Results from the Canadian Health Measures Survey

Abstract: BackgroundAlthough DDT [1,1,1-trichloro-2,2-bis(4-chlorophenyl)ethane] has been banned in many countries since the 1970s, it may still pose a risk to human respiratory health. In agriculture, DDT exposures have been associated with asthma and chronic bronchitis. However, little is known about the effect of DDT on lung function.MethodsWe used data on 1,696 participants 20–79 years of age from the Canadian Health Measures Survey (CHMS) and conducted multiple regression analysis to estimate associations between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Our finding that DDE affects pulmonary function in children is in agreement with two other investigations in adults, one from Denmark and one from Canada [ 21 , 22 ]. Both cohorts adjusted for height.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding that DDE affects pulmonary function in children is in agreement with two other investigations in adults, one from Denmark and one from Canada [ 21 , 22 ]. Both cohorts adjusted for height.…”
Section: Discussionsupporting
confidence: 93%
“…However, the odds of airway obstruction (defined as FEV1/FVC < 75%) were higher among offspring whose mothers had higher polychlorinated biphenyls, hexachlorobenzene, or DDE serum levels [ 21 ]. A Canadian study ( n = 1696) of adults aged 20–79 years of age demonstrated that lipid-adjusted DDE plasma concentrations were associated with a decline in FVC and FEV1 but not FEV1/FVC [ 22 ]. We are not aware of any investigation on DDE exposure and pulmonary function in children.…”
Section: Introductionmentioning
confidence: 99%
“…An investigation of community-dwelling individuals aged 40–80 years found that the incidence of chronic bronchitis was 12.7%, 12 and other studies observed similar results. 13 , 14 Though smoking is the most important risk factor, low socioeconomic class and urban living, 10 , 15 gender, asthma history, 16 changes in living habits, 14 odor or the musty smell of mildew/mold in the house, exposure to 1,1,1-trichloro-2,2-bis(4-chlorophenyl)ethane (DDT), 49 body mass index, 17 and air pollution 18 play roles in the development of chronic bronchitis. Studies have demonstrated that aging (especially >50 years old) is also a high risk factor for chronic bronchitis.…”
Section: Discussionmentioning
confidence: 99%
“…DDT (1,1,1-trichloro-2,2-bis[4-chlorophenyl]ethane) was banned worldwide in 2004 (subsequent to its discontinued use and/or banning beginning in the 1970’s). Still, recent results from the Canadian Health Measures Survey highlight the potential long-term harmful effects of this chemical that can persist in soil for decades [8]. In this report, DDT or its breakdown product DDE (1,1-bis-[4-chlorophenyl]-2,2-dichloroethene) were still readily detectable in nearly all participants (not selecting for pesticide use/exposure); while DDE plasma levels dose-dependently correlated with FEV 1 reductions.…”
Section: Copdmentioning
confidence: 99%